The Use of ICT Tools in Learning English Autonomously - Nduwimana, Arcade; Ndoricimpa, ClÃ©ment (JOLLT Journal of Languages and Language Teaching, 2023)
Over the past 40 years, there has been an increasing interest in learner autonomy. The present study was undertaken to examine the extent to which Burundians living in two major cities of the country use ICT tools and resources to improve their English autonomously. In doing so, the study first investigated the situations in which they need to use English and their current level of English regarding the different aspects. Adopting a descriptive research design, the study used a convenience sample of 239 subjects who were invited to respond to a questionnaire survey and participate in a two-day training on how to use ICT to learn English autonomously. The collected data were analysed using SPSS version 22. The findings indicated that participants still not exploit to the fullest the benefits of ICT to learn English autonomously. Indeed, 84.9% of the participants do not know what a podcast is and 66.1% of them report that they have no language learning applications on their smartphones. Besides, more than 60% of the participants have not yet tried to learn English using internet.Â  Yet, they feel the need to use English in different situations reflecting a vast range of domains such as Medicine, Law, Economy, etc. Findings also showed that the majority of the participants have a weak or very weak level regarding the different language aspects. Given these findings, it can be concluded that there is a need to raise awareness of Burundians to use ICT tools to learn English by themselves.